Clustered risk factors to health in children - Legnani, Rosimeide Francisco Santos; Legnani, Elto; Silva, Michael Pereira da; Gasparotto, Guilherme da Silva; Bacil, Eliane Denise Araújo; Campos, Wagner de (Medicina (Ribeirao Preto), 2015)
Study design: Cross-sectional descriptive correlational study. Objectives: To identify the prevalence of clustered Risk Factors to Health (RFH) in children from Curitiba, PR, as well as the association between clustered RFH and demographic variables. Methods: Was selected 1054 children (7-10 years) from public and private schools in Curitiba / PR. The assessment of Physical Activity (PA) was performed by 11 pictures to indicate the type of PA performed in a typical week (Webdafa electronic questionnaire). The scores sum of PA categories generated a General Physical Activity Score (GPAS: 0-187 points). Questions about screen time and sleep were added to Webdafa. Also was measured, body weight and height to calculate BMI (Body Mass Index). Data were categorized in insufficient level of physical activity (GPAS <84), screen time (> 2 hours / day), hours of sleep (<10 hours), and students were classified according to BMI in overweight or eutrophic. Results: Among those evaluated, 484 (45.9%) were boys, 548 (52%) studied during the afternoon, the age mean was 8.9 (± 0.9) years, body weight 33.5 kg (± 8.9), height of 1.36 m (± 0.08) and BMI 17.8 (± 3.4). Only 5.5% (58) children had one RFS, 35.1% (370) presented two RFH and 59.4% (626) of the children had 3 or more RFH in cluster form. Clustered RFH were significantly associated with the variables: gender, school type and class period in the day (p <0.005). Conclusion: There was a high prevalence of 2 or more RFH evaluated in children and association between clustered RFH with sociodemographic variables.